Efek Pendayaguanaan Wakaf Bagi Perekonomian - Fifit Iza Rosita; Moh. Anjas Radenta P; Fauziah Ernawati; Agus Eko Sujianto (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
The concept of waqf is based on ijtihad which can change time and place. Waqf assets are widely used to build facilities needed by the community such as places of worship, educational institutions as well as health centers. The purpose of this study was to determine the effect caused by the utilization of waqf assets on the community's economy. This type of research is qualitative research, with the method of studying literature and literature. Waqf has a positive impact on the economy if managed properly and effectively. This waqf property can be utilized for the benefit of various forms of implication. Starting from developing infrastructure to support people's lives, to providing real social and economic impacts for the community, so that it can be a good pulley to reduce poverty.